GREEN CHEMISTRY IN ACTION: DEVELOPING AND IMPLEMENTING A BIODEGRADABLE MATERIAL EXPERIMENT IN SENIOR HIGH SCHOOL SETTINGS - Sholahudin, Nabila Putri; Riandi, Riandi; Prima, Eka Cahya (INSECTA: Integrative Science Education and Teaching Activity Journal, 2024)
Teaching senior high school students green chemistry can contribute to future scientists and professionals who are responsible for safer, less hazardous chemistry. Plastic, known for its durability, affordability, and lightweight properties, is integral to daily life across industries, including housing, healthcare, fashion, sports, and transportation. However, the plastic industry poses significant economic and environmental challenges, raising concerns about its sustainability. To address these issues, this research focuses on the transformation of orange peel waste into a fine powder to develop a biobased, biodegradable plastic. The study conducted a soil burial test over a continuous 14-day period, revealing that an increased quantity of orange peel powder positively influenced the biodegradability of the bioplastic. Enhanced biodegradation was observed with higher concentrations of orange peel. The implementation of bioplastic experiments in the classroom received positive feedback from students, as evidenced by high ratings across various statements. Overall, the findings suggest that the experiments were not only engaging but also effective in shaping students' perspectives on plastic and science.